Monumento ou mentira histórica? As diferentes apropriações do local onde foram enterrados o Guia Lopes, Camisão e Juvencio e a construção do Cemitério dos Heróis da Retirada Da Laguna - Marin, Jérri Roberto [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2016)
The article analyzes the memory construction and multiple appropriations with the cemetery where Colonel Carlos de Moraes Camisão, Lieutenant-Colonel Juvencio Manoel Cabral de Menezes and Jose Francisco Lopes were buried during the Laguna Withdrawal (1865-1867). The cemetery and the tombs, built at the request of Alfredo Maria Adriano d'Escragnolle Taunay, became the center of debate in the 1920s, when the monument to the Heroes of Laguna and Dourados was designed. Later, with the transfer of the bodies, in 1941, the cemetery was deprived of the mortal remains of its most illustrious dead. However, since the the installation of the Highways Commission number 3, the cemetery and the graves have become revitalized in different contexts. New relationships between memory and identity were established when it became known as the Cemetery of the Laguna Withdrawal Heroes. In a second moment, this article adressed the process of patrimonialization in the Institute of National Historical and Artistic Heritage as well as the debates on whether it was a monument or a historical lie, i.e, around the graves and the cemetery were built, over several decades, different meanings, appropriations, and memory and identity relations.
Monument or historical lie? The multiple appropriations the place where they buried the bodies Guide Lopes, Camisão and Juvencio and construction of Laguna Withdrawal of the Heroes Cemetery
Keywords: Cemetery of the Laguna Withdrawal Heroes; Identity; Mato Grosso do Sul; Memory